Implementing translation techniques to develop students' vocabulary mastery: Evidence from an Indonesian vocational school - Nur’ Afiva Rahmayani; Nur Sehang Thamrin; Nirwana Nirwana; Jamiluddin Jamiluddin (University of Muhammadiyah Malang, 2026)
This study explores the implementation of translation techniques to enhance students’ vocabulary mastery in an Indonesian vocational school context. The research was conducted with eleventh-grade students at one of the state vocational schools in Palu, Indonesia focusing on three-word classes: nouns, verbs, and adjectives as essential components of English proficiency. Employing a quasi-experimental design, two groups were involved: an experimental class taught using translation-based strategies and a control class following the standard curriculum. Vocabulary mastery was measured through a researchers-developed test consisting of multiple-choice and fill-in-the-blank items. Instruction in the experimental group integrated literal and transposition translation techniques, combined with contextual reading and guided practice. The findings revealed that students exposed to translation techniques demonstrated significant improvement in vocabulary comprehension, retention, and contextual usage compared to the control group. The study concludes that translation serves as a practical and pedagogical tool for vocational education, bridging learners’ native and target languages while fostering confidence and engagement. Implications highlight the importance of integrating translation into English instruction for vocational students, as it supports both academic achievement and workplace readiness. These results provide valuable insights for teachers, curriculum developers, and future researchers seeking innovative strategies to strengthen vocabulary instruction in applied educational settings.